Perbandingan Math Anxiety dan Interest in Learning Mathematics Siswa Laki-laki dan Perempuan Sekolah Dasar di Pekanbaru - Mutiarsih, Fatma; Putra, Zetra Hainul; Syahrilfuddin, Syahrilfuddin (Universitas PGRI Palembang, 2023)
This research aims to figure out whether there is a comparison of math anxiety and interest in learning mathematics for male and female elementary school students in Pekanbaru. The method used in this research is the comparative survey method. The subjects of this research were 129 students (70 men and 59 women) from 3 schools in Pekanbaru. This research obtained that male students' math anxiety (72.9) was higher than female students (63.1) and male students' interest in learning mathematics (76.09) was also higher than female students (51. .85). The findings of this research show that there is a significant difference in math anxiety and interest in learning mathematics between male and female students.